2023
DOI: 10.48550/arxiv.2301.08878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Opioid Prescribing Limits on Drug Usage in South Carolina: A Novel Geospatial and Time Series Data Analysis

Abstract: To curb the opioid epidemic, states implemented opioid prescribing limits.• A novel geospatial model is proposed for classifying each opioid transaction.• The impact of opioid prescription limits varies among different proposed classes.• Geospatial model helps capture potential shortcomings of prescription limit policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous research has shown that state-level legislation can result in patients with opioid use disorder seeking prescribers in states with less stringent regulations [32]. In the context of this study, this phenomenon is equivalent to obtaining drugs from out-of-state distributors or shifting drug sales to out-of-state dispensers.…”
Section: Overallmentioning
confidence: 93%
“…Previous research has shown that state-level legislation can result in patients with opioid use disorder seeking prescribers in states with less stringent regulations [32]. In the context of this study, this phenomenon is equivalent to obtaining drugs from out-of-state distributors or shifting drug sales to out-of-state dispensers.…”
Section: Overallmentioning
confidence: 93%
“…It involves the planning, design, execution, monitoring, and control of all processes involved in the flow of goods and services from the initial sourcing of raw materials to the delivery of the finished product to the end customer [13]. The principles of supply chain management can be applied in various industries, including healthcare [14,15], retail, manufacturing, and transportation, to optimize the flow of goods, information, and resources, thereby improving efficiency and reducing costs [16]. Location allocation is a critical aspect of supply chain management, particularly in distribution and service industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Academic Buildings COG (1), COM (2), CPH (3), RA2 (4), M3 (5), ML (6), RAC (7), GSC (8), GH (9), BRH (10), SLC (11), OWE (12), HMN (13), MC (14), TC (15), KOC ( 16), C2 (17), EV3 (18), OPT (19), DC (20), SCH (21), FED (22), QNC (23), AL (24), HS (25), B2 (26), EV2 (27), REN (28), ESC (29), EV1 (30), STJ (31), EIT (32), HH (33), STP (34), Bl (35), PAS (36), CGR (37), E3 (38), EC3 (39), BMH (40), PHY (41), EC1 (42), LHI (43), NHI (44), EC2 (45), UC (46), LIB (47), ECH (48), ERC Athletic Buildings CLF (89), PAC (90).…”
Section: Segmentmentioning
confidence: 99%